Pengaruh Penerapan Arsitektur Hijau pada Adaptasi Penghuni terhadap Indekos Kafnath di Jakarta Timur - Abdul Fariq; Eva Elviana (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
The application of green architecture principles to boarding houses is an attempt to create a decent and sustainable dwelling. Green architecture connects occupants, buildings and the environment in a mutually beneficial relationship with minimal negative impacts. Kafnath boarding house in East Jakarta, which started operating in 2023, was chosen as a case study due to its diverse application of architectural principles. This study aims to determine the influence of green architectural principles on occupant adaptation in boarding houses. The method used was descriptive quantitative through a Likert scale questionnaire, analysed by multiple linear regression using SPSS. The results showed that the application of green architecture has a positive impact in the form of comfort and ease of adaptation, thus forming occupant loyalty during their stay.